Electrochemical Diffusion Study in Hydrogels - Eva Melnik; Steffen Kurzhals; Valerio Beni; Giorgio C. Mutinati; Rainer Hainberger (Proceedings)
In this study, poly(ethylene glycol) dimethacrylate (PEG-DMA)-based hydrogels were investigated with respect to the diffusion properties of methylene blue (MB) and MB conjugated proteins (MB-BSA and MB-IgG). Electrochemical sensors were used to monitor the diffusion process via the redox-active MB-label. All tested molecules showed good mobility in the hydrogel. Also, the release of MB-BSA could be demonstrated after drying the hydrogel containing MB-BSA, which is a promising result for the development of hydrogel-based reagent reservoirs for biosensing.